Exploring factors influencing students’ self-feedback: insights from a structural equation modeling analysis using an extended theory of planned behavior framework - Yang, Yongle; Yan, Zi; Zhu, Jinyu; Guo, Wuyuan; Wu, Junsheng; Huang, Bingjun (Frontiers in Psychology, 2025)
Empowering students as active agents in the feedback process is essential for students’ learning, which requires students to proactively seek, process, and use feedback to enhance their learning outcomes. Despite its critical significance in feedback research, there remains a notable gap in understanding the factors that motivate students to engage in the self-feedback process. This study applied an extended Theory of Planned Behavior (TPB) model to examine 1,311 students from mainland China regarding their self-feedback intentions and behaviors, along with crucial predictors (i.e., attitude, subjective norms, and perceived behavior control) with ten self-report scales. The psychometric properties of all scales were examined, and effects among factors were investigated using structural equation modeling. Findings reported that attitude, subjective norms, and perceived behavior control were significant predictors of students’ intentions for self-feedback, while perceived behavior control and intention notably influenced self-feedback behavior. Class climate, decomposed into individual-level (CCI) and group-level (CCG), had no significant impact on self-feedback intentions and mixed effects on self-feedback behavior. This study lays the groundwork for future efforts to promote meaningful self-feedback behavior, vital for fostering students’ metacognitive skills and lifelong learning.